Glucagon-like Peptide-1 receptor Tie2+ cells are essential for the cardioprotective actions of liraglutide in mice with experimental myocardial infarction - Brent A. McLean; Chi Kin Wong; M Golam Kabir; Daniel J. Drucker (Molecular Metabolism, 2022)
Objectives: Glucagon-like peptide-1 receptor (GLP-1R) agonists reduce the rates of major cardiovascular events, including myocardial infarction in people with type 2 diabetes, and decrease infarct size while preserving ventricular function in preclinical studies. Nevertheless, the precise cellular sites of GLP-1R expression that mediate the cardioprotective actions of GLP-1 in the setting of ischemic cardiac injury are uncertain. Methods: Publicly available single cell RNA sequencing (scRNA-seq) datasets on mouse and human heart cells were analyzed for Glp1r/GLP1R expression. Fluorescent activated cell sorting was used to localize Glp1r expression in cell populations from the mouse heart. The importance of endothelial and hematopoietic cells for the cardioprotective response to liraglutide in the setting of acute myocardial infarction (MI) was determined by inactivating the Glp1r in Tie2+ cell populations. Cardiac gene expression profiles regulated by liraglutide were examined using RNA-seq to interrogate mouse atria and both infarcted and non-infarcted ventricular tissue after acute coronary artery ligation. Results: In mice, cardiac Glp1r mRNA transcripts were exclusively detected in endocardial cells by scRNA-seq. In contrast, analysis of human heart by scRNA-seq localized GLP1R mRNA transcripts to populations of atrial and ventricular cardiomyocytes. Moreover, very low levels of GIPR, GCGR and GLP2R mRNA transcripts were detected in the human heart. Cell sorting and RNA analyses detected cardiac Glp1r expression in endothelial cells (ECs) within the atria and ventricle in the ischemic and non-ischemic mouse heart. Transcriptional responses to liraglutide administration were not evident in wild type mouse ventricles following acute MI, however liraglutide differentially regulated genes important for inflammation, cardiac repair, cell proliferation, and angiogenesis in the left atrium, while reducing circulating levels of IL-6 and KC/GRO within hours of acute MI. Inactivation of the Glp1r within the Tie2+ cell expression domain encompassing ECs revealed normal cardiac structure and function, glucose homeostasis and body weight in Glp1rTie2−/− mice. Nevertheless, the cardioprotective actions of liraglutide to reduce infarct size, augment ejection fraction, and improve survival after experimental myocardial infarction (MI), were attenuated in Glp1rTie2−/− mice. Conclusions: These findings identify the importance of the murine Tie2+ endothelial cell GLP-1R as a target for the cardioprotective actions of GLP-1R agonists and support the importance of the atrial and ventricular endocardial GLP-1R as key sites of GLP-1 action in the ischemic mouse heart. Hitherto unexplored species-specific differences in cardiac GLP-1R expression challenge the exclusive use of mouse models for understanding the mechanisms of GLP-1 action in the normal and ischemic human heart.